Treatment of Foot and Ankle Deformities Caused by Charcot-Marie-Tooth Disease: Clinical Cases - Tamulionytė, Gintarė; Kimtys, Vytautas (Lietuvos chirurgija, 2025)
Charcot-Marie-Tooth (CMT) disease is a genetic neurological disorder that affects the peripheral nerves, leading to impaired muscle strength and sensory function [1]. The disease is characterized by motor and sensory disturbances in the limbs, as well as foot deformities, most commonly pes cavus [2]. Due to amyotrophy in CMT, the muscles are unable to stabilize the joints, resulting in deformities. Improper joint positioning leads to abnormal loading, accelerated cartilage wear, osteoarthritis, and deformities such as equinus, cavus, varus, and valgus [3]. As there is no specific treatment for CMT, symptomatic management and rehabilitation are applied [4]. Surgical intervention is recommended in cases of severe deformities and joint osteoarthritis. Surgical options include soft tissue procedures, corrective osteotomies, arthrodeses, or ankle joint arthroplasty [7, 9, 10]. Early surgical intervention can halt the progression of deformities [17]. This article presents two cases of patients with CMT. The first patient developed cavovarus deformity and end-stage osteoarthritis of both the ankle and subtalar joints. Surgical treatment involved tibiotalocalcaneal (TTC) arthrodesis with an intramedullary nail. The second, younger patient developed cavovarus deformity, which was corrected through early surgical interventions, including bilateral calcaneal axis-correcting osteotomies, subtalar joint arthrodeses with screws, Achilles tendon lengthening, closed wedge osteotomies of the first metatarsals, and lateral ankle ligament reconstruction of the left foot due to ankle joint instability.
Keywords: Charcot-Marie-Tooth disease; osteoarthritis; arthrodesis